A comparative study of bidirectional ring and crossbar interconnection networks - Oi, Hitoshi; Ranganathan, N. (Computers & electrical engineering, 2002)
For distributed shared memory multiprocessors, the choice and the design of interconnection networks have a significant impact on their performance. Bidirectional ring networks are considered to be physically fast due to their simple structure, but topologically slow since their communication latency grows proportionally to the number of nodes. In this paper, we will present a quantitative measure to the question of how physically fast a bidirectional ring has to be to overcome its topologically slow communication latency by comparing it to the crossbar, an interconnection network that has opposite characteristics to the ring network. A hybrid method, in which workload parameters extracted from memory traces are given to an analytical model is used for performance evaluation. Our study shows for 16 nodes configuration, the performance of two networks are similar. For 32 and 64 nodes configurations, the bidirectional ring outperforms the crossbar by 21% and 61% respectively, on the average of four parallel applications.